2016
DOI: 10.1007/s00405-016-4145-8
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive histological imaging of head and neck squamous cell carcinomas using confocal laser endomicroscopy

Abstract: Confocal laser endomicroscopy (CLE) is an imaging technique that uses miniaturized fiberoptic probes to allow real-time histological imaging of human tissue. An application of CLE in otorhinolaryngology has hardly been investigated so far. In our study, we analyzed the applicability of CLE to visualize cancerous and healthy tissue of the head and neck region. Formalin-fixed tissue specimens from 135 head and neck squamous cell carcinoma (HNSCC) patients and 50 healthy controls were investigated using CLE with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 41 publications
0
26
0
4
Order By: Relevance
“…It allows the differentiation of epithelial cells, goblet cells and other pathological patterns 30 . The potential of staining agents of the nuclei in the head and neck region was examined by Linxweiler et al in formalin-fixed samples in 2016 18 . Acriflavin showed that it stained the nuclei while suppressing the autofluorescence of collagen fibres, only marginally improving the margin detection of tumours in the head and neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It allows the differentiation of epithelial cells, goblet cells and other pathological patterns 30 . The potential of staining agents of the nuclei in the head and neck region was examined by Linxweiler et al in formalin-fixed samples in 2016 18 . Acriflavin showed that it stained the nuclei while suppressing the autofluorescence of collagen fibres, only marginally improving the margin detection of tumours in the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…As they differ from other imaging techniques, the acquired images require the clinician or pathologist to have special training 15 . In the last few years, probe-based CLE has been intensively studied in gastroenterology and has expanded its application to other areas such as the head and neck, pulmonology and urology [16][17][18][19][20][21] . The aim of this study was to assess the diagnostic value of probebased CLE in identifying malignant lesions of the vocal cords in comparison to the accepted gold standard of histopathological examination.…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous studies have shown the applications of pCLE in vivo diagnosis of esophageal squamous cell carcinoma, biliary tract malignancies, as well as its advantages such as eliminating unnecessary biopsies, detecting tumor margins following resection, and allowing for immediate decision making . Furthermore, pCLE also has been used in the diagnostic differentiation between nonneoplastic, precancerous, and cancerous lesions of the head and neck …”
Section: Introductionmentioning
confidence: 99%
“…14 Furthermore, pCLE also has been used in the diagnostic differentiation between nonneoplastic, precancerous, and cancerous lesions of the head and neck. [15][16][17][18] The aim of our study was to depict the applicability of pCLE examination for diagnosing NPC in comparison to the gold standard of histopathological examination based on the morphology and architecture of the pCLE images.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several authors have reported the utility of probe‐based confocal laser endomicroscopy (pCLE) for evaluation of gastrointestinal cancer . Among fluorescent agents, acriflavine was able to stain the cell nucleus, and has been used effectively for diagnosing squamous cell carcinoma . However, there are safety concerns associated with acriflavine, including its potential carcinogenic activity.…”
mentioning
confidence: 99%